Regression Model of Processability Properties of Epoxidized Natural Rubber-Alumina Nanoparticle Composites (ENRAN) using Historical Data Design - M.Y, YUHAZRI; M, NORAIHAM; A.M, HAIRUL EFFENDY; M.O, SHAHRIZAN; M, ANDANASTUTI; J.G, JAMEELAH; M, DAHLAN; A, HUSNA (2012)
REFER TO FILE